2021
DOI: 10.3390/math9212678
|View full text |Cite
|
Sign up to set email alerts
|

User Evaluation of a Multi-Platform Digital Storytelling Concept for Cultural Heritage

Abstract: Digital storytelling platforms have proven to be a great way of bringing cultural heritage closer to people. What lacks is a deeper understanding of the user experience of such systems, especially in multi-platform digital storytelling. For the last three years, we have been developing a project called Spotlight Heritage Timisoara, which is at its core a digital storytelling platform for the city of Timisoara (Romania), soon to be European Capital of Culture in 2023. The project consists of a website, mobile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Spotlight Heritage Timisoara is a digital cultural initiative of the Politehnica University of Timisoara that reveals, through digital storytelling, the city of Timisoara through stories of cultural and historical heritage, communities, and neighborhoods, interwoven with the personal stories of the inhabitants of yesterday and today [34]. The initiative employs an interactive touchscreen table, desktop/laptop, mobile, and AR platforms.…”
Section: Related Workmentioning
confidence: 99%
“…Spotlight Heritage Timisoara is a digital cultural initiative of the Politehnica University of Timisoara that reveals, through digital storytelling, the city of Timisoara through stories of cultural and historical heritage, communities, and neighborhoods, interwoven with the personal stories of the inhabitants of yesterday and today [34]. The initiative employs an interactive touchscreen table, desktop/laptop, mobile, and AR platforms.…”
Section: Related Workmentioning
confidence: 99%
“…Users were asked to navigate in an audio-virtual spatialised soundscape composed of several different virtual rooms while listening to a story by using a tangible controller with different degrees of control over movement, audio spatialisation, and audio playback. In the study, the Immersive Response Questionnaire (IMX 13 ) was used to evaluate immersion and the Discrete Emotion Questionnaire (DEQ, [198]) to measure emotional content, along with Heart Rate with a non-intrusive device (a wearable band) showing an increased immersion and emotional content in conditions with spatial audio and controlled playback.…”
Section: Quality Of the Experience And Evaluationmentioning
confidence: 99%
“…Focusing on cultural heritage, disparate studies, and reviews are available on mixed reality storytelling [12,13], audio [6] and technology for audio AR [14]. However, very few comprehensive contributions that deal with these aspects altogether have been found.…”
Section: Introductionmentioning
confidence: 99%
“…The respondents were urged to adopt the think-aloud protocol while assessing the digital game images to provide better insight into distinguishing visual image identification and its relationship with visual style classification (Vert et al, 2021). Previous studies have shown that the think-aloud method supported the improvement of visual style descriptions from a visual terminology perspective (Krupke et al, 2019).…”
Section: Instrumentsmentioning
confidence: 99%